IMPERIALISM IN ASIA-PACIFIC: A STUDY OF U.S.-AFGHAN POLICY FROM 1935 TO 2015 - Imran Khan; Samad Khan; Ijaz Ul Haq (International Journal of Contemporary Issues in Social Sciences, 2024)
This research examines the trajectory of U.S.-Afghan policy from 1935 to 2015 within the framework of imperialism in the Asia-Pacific region. It delves into the historical, political, and economic dimensions of American intervention and influence in Afghanistan, analyzing how these factors reflect broader patterns of imperialism in Asia-Pacific. The study adopts a critical imperialist perspective, scrutinizing how U.S. policy objectives in Afghanistan have been shaped by strategic interests, including the control of resources, geopolitical positioning, and the assertion of global dominance. The research covers several pivotal periods: the early interactions between the U.S. and Afghanistan during the pre-Cold War era, the influence of Cold War dynamics on American policy, the impact of the Soviet invasion and subsequent U.S. support for Afghan resistance, and the post-9/11 era characterized by military intervention and nation-building efforts. Through a comprehensive review of diplomatic records, policy documents, and scholarly literature, the study assesses the implications of U.S. actions on regional stability, sovereignty, and local governance. By highlighting the continuity and shifts in U.S. policy, the research contributes to a deeper understanding of how imperialist strategies are operationalized in the context of Afghanistan and the broader Asia-Pacific region. It underscores the complex interplay between power, ideology, and geopolitical ambitions, offering insights into the enduring legacy of imperialism in shaping international relations and regional dynamics.